Theoretical study of fermi arc plasmons in Weyl semimetals - Xiong, Ying (2018)
Weyl semimetal is a type of crystals which host emergent quasiparticles that behave like Weyl fermions. In Weyl semimetals, the conduction band and the valence band cross at a single point in reciprocal space called the Weyl point. Quasiparticles near this point can be described by the Weyl equation. The Weyl points have an intrinsic chirality and are topologically protected. On the exposed surface of Weyl semimetals, there exist exotic surface states which form an open segment (the Fermi arc) joining a pair of Weyl points with opposite chirality which are gapped in bulk. In this report, we show that the Fermi arc states give rise to unusual properties of surface plasmon dispersion, including non-reciprocality and broken time-reversal symmetry. As a result of the hybridization of conventional surface plasmon modes with collective modes associated to Fermi arc states, the Fermi arc plasmon (FAP) dispersion splits into three branches of solutions. At large wave vectors, the dispersion features open hyperbolic iso-frequency contours, which allows for tightly collimated beams of FAPs propagating in two specific directions with a broad bandwidth. This phenomenon may serve as a signature of Fermi arcs and can be used to detect and probe new Weyl semimetals. Furthermore, the intrinsic hyperbolic modes make Weyl semimetals promising candidates for high resolution subwavelength imaging with hyperlenses.